The complete mitochondrial genome of Silurus grahami Regan, 1907 (Siluriformes: Siluridae), a native catfish in Fuxian Lake. Issue 3 (4th March 2021) - Wu, Junjie; Lei, Chunyun; Zhao, Jingxia; Jin, Fangpeng; Gao, Haitao; Fu, Shiwei; Zhou, Rui; Luo, Yongxin; Leng, Yun; Xue, Shaowei; Zhang, Wenkui; Li, Guanghua
Abstract: In this study, the whole mitochondrial genome of Silurus grahami was reported to be 16, 518 bp in length, including 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and one control region. The phylogenetic analysis based on 13 protein-coding genes showed that S. grahami was sister to clade of S. meridionalis and S. lanzhouensis . A total of 81 bases differences were identified in COI barcoding region, which could be used for species identification in catfish.